Experimental Study and Reliability Analysis of Flexural Capacity of RC Beams Reinforced with 600 MPa Grade Steel - Xianhua Yao; Yulong Zhang; Junfeng Guan; Lielie Li; Haichao Liu; Ruicong Han; Junyi Xi (Advances in Civil Engineering)
Flexural capacity of beams reinforced with 400 or 500 MPa grade steel can be accurately estimated by using equations provided in design codes. Recently, 600 MPa grade steel has evolved in the construction industry, and the applicability of existing equations for this grade of steel should be verified by performing experimental investigation. By conducting tests on concrete beams reinforced with 600 MPa grade high-strength steel, this study investigates the flexural performance for different concrete strength grades and different reinforcement ratios. Flexural capacities of concrete beams reinforced with 400 MPa, 500 MPa, and 600 MPa grade steel are analyzed based on equations in various codes and based on experimental studies in the literature. Furthermore, this study performs reliability analysis and verifies the three design values of 600 MPa grade steel yield strength in relation to the experimental performance and recommends the appropriate design values of 600 MPa grade steel yield strength. Research results show that when the measured values of yield strength of the steel bars and concrete strength are used, the ratio of the measured failure moment value to the calculated value for various beams based on different codes is nearly 1.0, demonstrating the high degree of fitting. Finally, the reliability analysis shows that the design yield strength of the 600 MPa grade high-strength steel bars should be taken as 520 MPa.